Drones in the mining industry - Nalobina, O. O.; Holotiuk, M. V.; Bundza, О. Z.; Налобіна, О. О.; Голотюк, М. В.; Бундза, О. З. (Norwegian Academy of Science, 2024)
Unmanned aerial vehicles (UAVs) are becoming more and more commonplace in our lives. The use of UAVs in many industries where they are capable of performing complex tasks has become relevant. An important industry is mining, which requires constant monitoring of the correct and complete development of deposits, occupational safety, hazardous emissions, etc. New technologies based on the use of UAVs can solve these problems. The article analyzes the possibilities of using UAVs in the mining industry based on the analysis of existing research.

Безпілотні літальні апарати (БПЛА) все більше входять у наше життя. Актуальним стало викорис-тання БПЛА у багатьох галузях промисловості, де вони здатні виконувати складні завдання. Важлива га-лузь – гірничодобувна потребує постійного контролю за правильним і повним відпрацюванням покладів, безпекою праці, небезпечними викидами, тощо. Вирішити ці проблеми можуть нові технології, які базу-ються на використанні БПЛА. У статті проаналізовано можливості використання БПЛА у гірничодобувній промисловості на основі аналізу чинних досліджень.
Keywords: unmanned aerial vehicle; mining industry; analysis; безпілотний літальний апарат; гірничодобувна галузь; аналіз